Enhancing Low-Frequency Model for Post-Stack Inversion using Geostatistics: A Case Study in Imaging Carbonate Structure - Dimas Pramudito; Azhar Harisandi; Rebecca Putri Sinaga; Fitriah Nuraeni (Himpunan Ahli Geofisika Indonesia (HAGI), 2021)
Post-stack model based seismic impedance inversion can be a fast and efficient first step in deriving reservoir properties based on seismic data. It can further be used as an input for quantitative interpretation, however behind that seemingly oversimplified process we should not forget the nature of bandlimited seismic data and how we should carefully extract and model the low-frequency component. In the worst case, the low frequency or background impedance model (LFM) might not even be possibly recovered due to the limited logging data interval. In this paper, we will demonstrate how to create an absolute impedance volume to delineate porous reefal carbonate reservoir that has low acoustic impedance by accurately constructing a low frequency model aided with cokriging. The result is an LFM that can accomodate all available well data but still honoring local geological structures and continuities.